John Coughlin, Law, Person and Community, Oxford University Press, New York 2012 - Feczko, Piotr (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The review of John J. Coughlin’s book Law, Person and Community was written especially for secular lawyers, who don’t specialize in canon law. The main task of the author of the book is the presentation of the three basic concepts mentioned. The three issues count among the elementary problems of modern law (especially for public and family law) and social life. The author’s point of view is related to canon law, traditional religions (Christianity, Judaism and Islam) and natural law. The additional issues presented here are: an interaction between civil (secular) and canon law and the intentionality of both laws. The author presented a unique art of dialogue between canon law and secular law. In particular, J. Coughlin claims that: 1) canon law comes from divine authority and is based on natural law (it differs from secular law); 2) natural and theologic foundations of canon law are a better foundation for human rights than positive and relative logic, which is based (only) on legal or political order; 3) there are many common points of traditional religions with reference to the problems of legal theory and practice; 4) canon law is a constructive conversation partner in discussions regarding legal sciences.
Keywords: prawo kanoniczne; filozofia prawa; prawo porównawcze; prawo naturalne